Effects of the precipitation of secondary phases on the erosion-corrosion of 25% Cr duplex stainless steel. (15th May 2019) - Kim, Young-Jae; Kim, Su-Won; Kim, Han-Byeol; Park, Choong-Nyeon; Choi, Yun-Il; Park, Chan-Jin
Graphical abstract: Highlights: The effects of aging at 850 °C on the precipitation of secondary phases and the erosion-corrosion behavior of 25% Cr duplex stainless steel were studied. An aging time of 30 min is regarded as a boundary aging condition for erosion-corrosion. A current density response of ˜0.8 mA cm −2 is considered to be a criterion for surface depassivation after the initial erosion-corrosion. Abstract: This study examined the effect of aging at 850 °C on the precipitation of secondary phases and the resultant erosion-corrosion behavior of 25% Cr duplex stainless steels (DSS). An aging time of 30 min, which led to a ratio of reactivation current to activation current ( ir /ia × 100) of ˜1% in a DL-EPR test and a current density of ˜0.8 mA cm −2 at 9 m s −1 in a jet impingement test, is regarded as a boundary aging condition for erosion-corrosion. Further, the current density response of ˜0.8 mA cm −2 can be considered a criterion for the surface depassivation resulting from erosion-corrosion.